Students' Students' Ability in Writing Narrative Text through Concept Mapping Implementation at the Eighth Grade of SMP Negeri 2 Mandrehe Utara: Introduction, Research Methodology, Results and Discussion, Conclusion, and References - Elvi; Yasminar Amaerita Telaumbanua; Trisman Harefa; Hidayati Daeli (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2025)
English is one of the essential subjects that students must master, particularly in writing skill. However, the reality 22 eighth grade students at SMP Negeri 2 Mandrehe Utara still had difficulties in writing good and structured narrative texts. This was due to the lack of learning strategys that support students in organizing their ideas. Therefore, this study aimed to describe students’ ability in writing narrative texts through the implementation of concept mapping that is valid, practical, and effective. This research used a descriptive qualitative approach with a case study design. Data were collected through observation, written tests, interviews, and documentation. The results showed that the use of concept mapping helped students to organize ideas systematically, understand the structure of narrative texts, and develop more coherent storylines. The teacher provided sufficient guidance, although written evaluations and individual feedback were not yet optimal. Most students showed improvement in narrative writing, especially in composing orientation, complication, and resolution. However, some students still found it difficult to develop creative conflicts and conclusions. The study concluded that concept mapping is an effective learning strategy to support the process of writing narrative texts. Therefore, it is recommended that teachers consistently apply this strategy and complement it with comprehensive evaluation to achieve better learning outcomes.